Analysis of the Influence of Motivation, Job Satisfaction, Leadership, and OCB in the Manufacturing Industry of Batam City - Jacelyn Christina Yeo; Muhammad Donal Mon (Jurnal Manajemen (Edisi Elektronik), 2025)
Human resources are an important asset for companies, especially in the manufacturing sector. The manufacturing industry in Batam City contributed 56.83% to the Regional Gross Domestic Product (GDP) in 2023, significantly impacting unemployment rate by ab-sorbing a large-scale workforce with various skill levels. This study aims to analyze the influence of motivation, job satisfaction, and leadership on Organizational Citizenship Behavior (OCB) in Batam’s manufacturing industry. A quantitative approach was used in this study, collecting data from employees through ques-tionnaires distributed via Google Forms from October 2023 to March 2024, with a sample size of 410 respondents. The data was analyzed using Smart PLS 3.2.9 software. The result showed that motivation did not significantly influence OCB, while job satisfac-tion and leadership had a significant influence on OCB. Motiva-tion was also found to have a significant influence on job satisfac-tion and leadership. Indirectly, motivation affects OCB through job satisfaction and leadership. Management in Batam’s manufac-turing industry should focus on improving job satisfaction and leadership quality to enhance OCB, considering strategies such as incentives, career development, opportunities, and a supportive work environment. Future research should expand its scope to various industries and locations to gain a more comprehensive understanding of the factors affecting OCB.